ESG development of Russian companies: a focus on the markets of the Asian-Pacific region and the Middle East - E. B. Starodubtseva; M. B. Trachenko (Вестник университета)
The article considers the tasks of the ESG transformation in Russian companies. Particular attention is paid to the analysis of the main problems and development trends of the ESG agenda in the regions where Russian business is reorienting in conditions of the sanctions’ pressure, namely, the countries of the Asia-Pacific region and the Middle East. The expediency of adopting a single national standard for non-financial reporting, which includes a system of indicators taking into account industry specifics and allows optimizing partnerships with Eastern counterparties, is substantiated. It is proposed to create an ESG portal under the auspices of VEB.RF as the main methodological center for sustainable development in the Russian Federation, which will allow Russian exporters and importers to receive up-to-date information on the ESG requirements of potential foreign counterparties. The basis for financing for the creation and development of such a portal should be both federal budget funds and private financing, which corresponds to the interests of both parties. Thus, the state encourages the development of export relations with foreign companies, and the private sector gets access to regularly updated information to expand foreign economic activity in new markets. Further research will be aimed at developing recommendations for Russian exporters and importers focusing on the markets of the Asia-Pacific region and the Middle East in the context of specific jurisdictions and industries.